Effect of gibberellic acid on the quality of chrysanthemum (Dendranthema grandiflora L.) cv. Faroe - da Silva Vieira, Marcos Ribeiro [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; de Souza, Angela Vacaro [UNESP]; Costa, Paula Nepomuceno [UNESP]; Guimaraes Santos, Caio Marcio [UNESP]; Alves, Leonardo de Sousa; de Oliveira, Nelson Geraldo [UNESP] (Academic Journals, 2011)
The aim of the present work was to evaluate the quality of chrysanthemum cultivar Faroe, subjected to different gibberellic acid (GA(3)) concentrations applied to the field. The treatments were composed of four doses of GA(3) (0, 15, 30 and 45 mg L-1) applied at the beginning of the formation of buttom floral (28 days after transplanting of seedlings). According to the results, a single low concentration of GA(3) application did not interfere with the phenotypic characteristics of the chrysanthemum cultivar Faroe.
Keywords: Dendranthema grandiflora; height; diameter; flowering